Pengaruh Pendidikan Kewirausahaan Dan Kepercayaan Diri (Self Confidence) Terhadap Minat Berwirausaha Mahasiswa Pendidikan Ekonomi Angkatan 2021-2023 Universitas Pgri Wiranegara (International Forum of Researchers and Lecturers, 2026)
Students' perspectives and readiness to start a business are greatly influenced by entrepreneurship education. The purpose of this study was to investigate how the entrepreneurial desire of 64 Economics Education students at PGRI Wiranegara University is influenced by entrepreneurship education and self-confidence. Based on the findings of the quantitative study, self-confidence and entrepreneurship education both significantly influence entrepreneurial desire, both separately and together. It has been proven that self-confidence (t-test 2.224) and entrepreneurship education (t-test 5.098) have an influence. Both factors have a significant impact simultaneously, as indicated by the calculated F value of 58.933. Furthermore, based on the analysis of the coefficient of determination (R Square), these two variables contribute 65.9% of entrepreneurial interest, while other factors influence the remaining 34.1%. This conclusion is important and can be a guide for future research on entrepreneurship teaching techniques.